2019
DOI: 10.1161/circulationaha.118.035831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patisiran, an RNA Interference Therapeutic, on Cardiac Parameters in Patients With Hereditary Transthyretin-Mediated Amyloidosis

Abstract: Background: Hereditary transthyretin-mediated (hATTR) amyloidosis is a rapidly progressive, multisystem disease that presents with cardiomyopathy or polyneuropathy. The APOLLO study assessed the efficacy and tolerability of patisiran in patients with hATTR amyloidosis. The effects of patisiran on cardiac structure and function in a prespecified subpopulation of patients with evidence of cardiac amyloid involvement at baseline were assessed. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
267
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 373 publications
(283 citation statements)
references
References 28 publications
9
267
0
7
Order By: Relevance
“…Therefore, the possibility, as highlighted by the present report, of diagnosing ATTR‐AC in patients mostly with few symptoms may represent a striking opportunity in order to offer tafamidis treatment to a greater number of subjects expected to benefit from it, altering significantly the course of their disease. Medications that silence TTR production have also shown some preliminary positive results, but their investigation so far has been limited to ATTRv‐AC patients of younger age and with milder disease as compared to the ATTR‐ACT and RW ones analysed here . Interestingly, the pre‐defined proportion of ATTRv/ATTRwt‐AC of ATTR‐ACT was replicated by chance in our RW population, in which ATTRv‐AC was mostly related to Ile68Leu, Val122Ile and Val30Met late‐onset mutations.…”
Section: Characteristics Of Transthyretin Amyloid Cardiomyopathy Triamentioning
confidence: 70%
“…Therefore, the possibility, as highlighted by the present report, of diagnosing ATTR‐AC in patients mostly with few symptoms may represent a striking opportunity in order to offer tafamidis treatment to a greater number of subjects expected to benefit from it, altering significantly the course of their disease. Medications that silence TTR production have also shown some preliminary positive results, but their investigation so far has been limited to ATTRv‐AC patients of younger age and with milder disease as compared to the ATTR‐ACT and RW ones analysed here . Interestingly, the pre‐defined proportion of ATTRv/ATTRwt‐AC of ATTR‐ACT was replicated by chance in our RW population, in which ATTRv‐AC was mostly related to Ile68Leu, Val122Ile and Val30Met late‐onset mutations.…”
Section: Characteristics Of Transthyretin Amyloid Cardiomyopathy Triamentioning
confidence: 70%
“…Patients were previously classified as NYHA class I (40%) and NYHA class II (60%), whilst patients with higher classes were excluded. The exploratory endpoints comprised echocardiographic parameters, as well as cardiac biomarkers NT‐proBNP and troponin I. Patisiran induced an average reduction in left ventricular wall thickness of −0.9 mm ( P = 0.017) compared to baseline, along with reductions in interventricular septal thickness and left ventricular mass . In consideration of the mostly unchanged values for patients receiving placebo, these results indicate that patisiran may lead to the reversal of structural changes in the myocardium, typically evoked by amyloid deposition.…”
Section: Clinical Efficacy – What Do We Know So Far?mentioning
confidence: 95%
“…If pharmaceuticals are not discussed in this section, no valid clinical data are available at this point to the best of our knowledge. A summary of all trials taken into consideration can be found in Table (polyneuropathy) and Table (cardiomyopathy) …”
Section: Clinical Efficacy – What Do We Know So Far?mentioning
confidence: 99%
See 1 more Smart Citation
“…The APOLLO phase 3 trial proved that patisiran was beneficial to patients with hereditary transthyretin amyloidosis. The approval of patisiran may finally lead to the development of RNAi drugs . Nanoparticle‐mediated siRNA treatment is expected to be an alternative to chemotherapy for lung cancers.…”
Section: Introductionmentioning
confidence: 99%